2021
DOI: 10.21037/qims-20-337
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET-based radiomics model for predicting occult lymph node metastasis in clinical N0 solid lung adenocarcinoma

Abstract: Background: This study aimed to develop a preoperative positron emission tomography (PET)-based radiomics model for predicting occult lymph node metastasis (OLM) in clinical N0 (cN0) solid lung adenocarcinoma. Methods: The preoperative fluorine-18-fludeoxyglucose ( 18 F-FDG) PET images of 370 patients with cN0 lung adenocarcinoma confirmed by histopathological examination were retrospectively reviewed. Patients were divided into training and validation sets. Radiomics features and relevant data were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 42 publications
1
31
0
1
Order By: Relevance
“…Lobectomy and systematic lymph node dissection are standardized treatments for invasive lung cancer (1). Due to improved recovery after surgery, the average length of stay for lobectomy has decreased to 1 to 2 days postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Lobectomy and systematic lymph node dissection are standardized treatments for invasive lung cancer (1). Due to improved recovery after surgery, the average length of stay for lobectomy has decreased to 1 to 2 days postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…However, the measurement of solid tumor size differed using different software and among the different observers (28,29). 18 F-FDG PET-CT integrates anatomical and metabolic information and is currently the primary tool for staging NSCLC (30), and previous studies have demonstrated that SUV max was related to VPI, LVI, and LNM. Tsutani et al (31) reported that the SUV max on 18 F-FDG PET-CT helped predict pathological invasiveness in clinical stage IA lung AC and 18 F-FDG uptake was closely related to solid tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore necessary to develop a novel signature to improve the prediction of death or recurrence risk in patients with LUAD. Radiomics is an emerging technique that converts conventional medical images into high dimensional features, providing valuable data to develop noninvasive signatures for cancer prognosis (12,42,43). Compared with tumor phenotypic radiomic features derived from CT or PET/CT, which are sensitive to the multicenter effect (28), metabolic features are more repeatable and reproducible across multicenter cohorts and are more suitable for clinical application.…”
Section: Discussionmentioning
confidence: 99%